Measures on Chinese Products in Indonesia during the Covid-19 Pandemic: Why was Anti-Dumping Action Imposed? - Amanda, Andi Putri; Wardah, Wardah (Udayana Journal of Law and Culture, 2022)
During the Covid-19 pandemic, the Government of Indonesia (GoI) issued policies to keep the situation under control, particularly in the trade sector, with the goal of protecting the state from fraudulent acts of business actors dumping practices. T he Indonesian Anti-Dumping Committee (KADI ) has investigated Chinese products that cause harm to domestic products, namely Lysine and Hot Rolled Coil of Another Alloy. This article discusses the implementation of anti-dumping action conducted by the KADI, and the challenges that are faced in the performance of anti-dumping action . It is based on normative legal research that applies statutory and conceptual approach es . T he results show t hat KADI’s scientific investigation succeed in proving the causal link between certain imported Chinese products and the injury in Indonesian local i ndustries . T he re are three challenges faced by KADI in investigating the a nti- d umping action . First, the W ork Fr om H ome system hampered them from coll e cting the data . Second, a lack number of capable staf f to investigate the evidence of dumping in Indonesia . Third, the Regulation of Minister of F inance No. 103/PMK.010/2020 suspen d the import duties on all imported products that enter the Indonesian market from September , 22 until December 31, 2020 .